The Role of Financial Depth Indicators in Achieving Banking Stability - An Analytical Study of the Iraqi Banking Sector (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research aims to analyze the mutual impact between financial depth and banking stability indicators in Iraq during the period (2014-2023), by building a standard model to test the partial (sub) and complex (total) relationships between these indicators, Accordingly, three indicators of financial depth were used, namely (credit to GDP, household sector credit, credit to deposits) and three indicators of banking stability, namely (capital adequacy, liquidity coverage, and non-performing loans). The research relied on the descriptive analytical approach with the use of standard models via the Eviews program, the results showed a significant correlation and impact between the composite financial depth index and the composite banking stability index. The results confirmed that the credit-to-deposit ratio has the greatest impact on banking stability indicators, whether positively (in liquidity coverage) or negatively (in capital adequacy and the banking default rate). The study recommends improving credit quality and expanding financial inclusion, thus enhancing the long-term resilience of the banking system.
Keywords: Financial Depth; Banking Stability; Credit to Deposit